2014
DOI: 10.3928/1081597x-20140815-02
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability, Reproducibility, and Agreement Between Three Different Scheimpflug Systems in Measuring Corneal and Anterior Segment Biometry

Abstract: Reliability was good to excellent in the three devices for all measured variables. Interdevice agreement analysis suggests that measurements for anterior radius of curvature, central corneal thickness, and anterior chamber depth, but not for maximum anterior and posterior corneal elevation and total higher-order aberrations, from the Sirius 3D and Galilei G2 can be interchangeable with the Pentacam HR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
40
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 29 publications
9
40
2
2
Order By: Relevance
“…Nam et al [7] reported a TRT and CoV of CCT of 10.0 mm and 0.67%, respectively, using the Pentacam. Hernández-Camarena et al [18] demonstrated strong repeatability of CCT measurements using the Sirius, and similar results were reported by Maresca et al [19]. Some studies also showed good repeatability and reproducibility from the Galilei.…”
Section: Discussionsupporting
confidence: 63%
“…Nam et al [7] reported a TRT and CoV of CCT of 10.0 mm and 0.67%, respectively, using the Pentacam. Hernández-Camarena et al [18] demonstrated strong repeatability of CCT measurements using the Sirius, and similar results were reported by Maresca et al [19]. Some studies also showed good repeatability and reproducibility from the Galilei.…”
Section: Discussionsupporting
confidence: 63%
“…The differentiation between normal and abnormal patterns of corneal topography is, today, well sustained by the definition of different corneal topography and corneal aberrometry indices and corneal volumetric and densitometry data, among others [36]. However, the geometrical characterization indices proposed by these devices are not easily compatible between different tomographers, generating confusion in the ophthalmic community [8].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous quantitative geometric descriptors of the corneal surfaces for the diagnosis of ectasia and provided by corneal tomographers can be found in the scientific literature [5]. However, the values obtained for these descriptors vary depending on the tomographer used [8], preventing their widespread acceptance and clinical utility.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have assessed the repeatability of various anterior segment measurements provided by the same Scheimpflug imaging-based system as that used in the current study [6][7][8][9][10], with most reporting high levels of consistency [10][11][12][13][14]. However, few works have studied the repeatability of IA measurements [8], and to date, there is no study validating the consistency of measurements provided by the glaucoma mode of the Scheimpflug imagingbased system used in our series.…”
Section: Discussionmentioning
confidence: 99%
“…One example of a system providing non-invasive measurement of the IA is the Sirius ® system (Costruzione Strumenti Oftalmici [CSO], Florence, Italy), a non-contact 3D rotating Scheimpflug camera combined with a Placido ring that provides different anatomical measurements of the anterior segment. While there is strong scientific evidence of the consistency and repeatability of anterior segment measurements provided by this system in healthy and even pathological eyes [6][7][8][9][10][11][12][13][14][15], evidence of the repeatability of IA measurements is limited [8]. Likewise, to the best of our knowledge, no studies have evaluated and compared the consistency of IA measurements at different nasal and temporal meridians using this device.…”
Section: Introductionmentioning
confidence: 99%